Soil tillage systems, cover crops and productivity in cassava - Otsubo, Auro Akio; Mercante, Fábio Martins; Silva, Rogério Ferreira da; Borges, Clovis Daniel (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the effects of cover crops and soil tillage systems in the development and yield of cassava (Manihot esculenta Crantz). The experiment was carried out in an Arenic Hapludult under conventional tillage, and in a minimum tillage system over mucuna (Stizolobium cinereum Piper & Tracy), sorghum [Sorghum bicolor (L.) Moench] and millet straw [Pennisetum americanum (L.) K. Schum.]. Eighteen months after cassava planting, the following variables were evaluated: plant height, shoot dry matter production, number of roots, yield, dry matter and starch content on storage roots, and harvest index. It was observed that conventional tillage could be replaced by minimum tillage in cassava crop, when associated to cover crops use, since it leads to a significant increase in cassava yield, particularly when using millet as cover crop. The use of cover crops before cassava cultivation, in a minimum tillage system, is an efficient alternative for a better crop management.